Pelaksanaan Program Smart Transport Sekolah di Kota Mojokerto Tahun 2017 The Implementation of School Smart Transport Program in Mojokerto City in 2017) - Kurniasari, Nia Mega; A, Ardiyanto; Makmur, Hadi (University of Jember, 2019)
AbstractThisstudy aims to describe the implementation of School Smart Transport Program inMojokerto City in 2017. This descriptive stu dy employed a qualitative approach. Datawere collected through observation, interviews, and documentation. Then, the data wereanalyzed by using interactive analysis of Miles and Huberman which consisted of datareduction, data presentation, and drawing c onclusion. To test the data validity,researchers used source and technique triangulations. The theory used to analyze theimplementation of School Smart Transport Program was owned by Van Meter and VanHorn with six variables namely standard and policy ta rget, resource, characteristics ofimplementing organization, communication between implementing organizations,communication between related organizations, implementing activities, and social,economic and political environments. Based on the findings, th e implementation ofSchool Smart Transport Program run in accordance with the established track or route,but the Mojo E Transchool application was not optimally used by the community.Keywords: i mplementation , program, and School Smart Transport